Local micro-mechanical stress conditions leading to pore nucleation during dynamic loading. (February 2021) - Bronkhorst, C.A.; Cho, H.; Marcy, P.W.; Vander Wiel, S.A.; Gupta, S.; Versino, D.; Anghel, V.; Gray, G.T.
Abstract: Accurately representing the process of porosity-based ductile damage in polycrystalline metallic materials via computational simulations remains a significant challenge. The heterogeneity of deformation in this class of materials due to the anisotropy of deformation of individual single crystals creates the conditions for the formation of a damage field. In this work, a technique of soft-coupled linkage between a macro-scale damage model and micro-mechanical calculations of a suite of polycrystal realizations of a representative BCC tantalum is presented. The macro-scale model, which accounts for rate-dependence and micro-inertial effects in the material, was used to represent two plate impact experiments and predict the point in time in the loading profile when porosity is initiated. The three-dimensional loading history from the macro-scale calculation was then used to define the probable loading history profile experienced within the samples. A micro-mechanical model based on an accurate representation of single crystal plasticity is then presented. Specifically, this model is employed in performing of polycrystal calculations of statistically representative microstructures of the tantalum material subjected to the extreme loading conditions informed from the macro-scale calculations. This enables to provide local-scale stress conditions for porosity initiation within the polycrystalline network. Furthermore, the micro-mechanical model captures the non-Schmid effects that accounts anomalous motion of the dominant screw dislocations within each of the single crystals. The results of the micro-mechanical simulations suggests that the non-Schmid effects significantly influence the local stress conditions across grain boundaries and triple junctions within the polycrystalline network. The computational results also suggest that the von Mises stress conditions and triaxiality at the grain boundaries and the grain boundary triple lines are highly variable but the variability is reduced with distance to the grain center. Furthermore, we found that the stress conditions at the grain boundaries are strongly dependent on the orientation of each boundary with respect to the shock direction. Highlights: In this work, a technique of soft-coupled linkage between a macro-scale damage model and micro-mechanical calculations of a suite of polycrystal realizations of a representative BCC tantalum is presented. A micro-mechanical model is used for polycrystal calculations of statistically representative microstructures subjected to loading conditions from macro-scale calculations. The computational results suggest that von Mises stress conditions and triaxiality at grain boundaries and triple lines are highly variable but variability is reduced with distance to the grain center.